Larvicidal Activity and Histopathological Effect of Averrhoa bilimbi Fruit Extract on Aedes aegypti from Surabaya, Indonesia - Etik A. Rohmah; Sri Subekti; Marcellino Rudyanto (Journal of Parasitology Research, 2020)
Averrhoa bilimbi has been long thought to have biological activity. The aim of this study was to determine the activity of primary and secondary metabolites from A. bilimbi fruit extract on Aedes aegypti larvae mortality and midgut histopathology. Experiment was performed to third-instar Ae. aegypti larvae collected from Surabaya, which then exposed to A. bilimbi crude fruit extract at various concentration for 24 hours. After exposure, larvae were evaluated of its mortality and fixed in 2.5% neutral buffer formalin before processed and sectioned into histological slides and stained with hematoxylin-eosin (HE). Statistical analysis was performed using Spearman rank correlation to determine histopathological damage on midgut of Ae. aegypti larvae. Phytochemical screening of A. bilimbi crude fruit extract found that it contained saponins, tannins, and terpenoids. Minimum concentration able to induce mortality on Ae. aegypti larvae (LC50) was 977 ppm, while LC90 was at 1380 ppm. Severe alteration of larvae midgut was found after 24 hours exposure to 2000 ppm extract. Features of damage mostly found in larvae midgut were disruption of the microvilli, columnar cell vacuolization, epithelial nucleus crossed midgut lumen, and basal membrane damage. Damage caused by fruit extract in midgut of Ae. aegypti third instar larvae inhibited development of larvae. This study reported first finding of histopathological effect of A. bilimbi fruits extract on Ae. aegypti larvae midgut. Result of study was expected to contribute to better understand extract bioactivity of this plant to be applied as natural larvicide for Ae. aegypti.